ASSOCIATION BETWEEN THE PRESENCE OF ODONTOGENIC INFLAMMATORY CYSTS AND SYSTEMIC IMMUNE RESPONSE BEFORE AND AFTER THEIR SURGICAL THERAPY - Stojanova, Irena; Mirjana, Markovska Arsovska; Vanco, Spirov; Maja, Dimitrova Popovska; Zhaklina, Mencheva; Biljana, Evrosimovska (Journal of Morphological Sciences; Vol 7 No 3 (2024): JMS, 2024)
Odontogenic inflammatory cysts are pathological lesions that are often present in clinical practice and they represent potential focal points with an impact on other organs and systems in the body. The aim of the study is to determine the association between the presence of odontogenic inflammatory cysts and the systemic immune response. 63 patients diagnosed with odontogenic inflammatory cysts were included in the study and divided into three groups (Group 1-patients with radicular cysts-23, Group 2-patients with residual cysts-20 and Group 3-patients with periodontal cysts-20). Values of IgA, IgM and IgG in serum were examined before and one month after the surgical therapy in the device Cobas 6000 model c501 (Roche, Germany). In all three investigated parameters of humoral immunity (IgA, IgG and IgM in serum), in patients IgA and IgG values before and one month after the intervention in the three groups of patients did not indicate a significant difference for a consequent (p=0.4352 vs p=0.4090), (p=0.1489 vs. p=0.2456). The comparison of the three groups of patients regarding the level of IgM in serum indicated a significantly higher value of this parameter in patients before the intervention (p=0.0006) as well as one month after the intervention (p=0.0120) and significant difference in periodontal compared to residual cysts (p=0.0061) Surgical intervention of odontogenic inflammatory cysts (cistaectomio in toto) affected the values of systemic immunoglobulins, especially the differences in IgM levels. These findings suggest that IgA, IgG, and IgM may play an important role in the occurrence, development, and persistence of cystic lesions Keywords: Odontogenic inflammatory cysts, immunological analysis, systemic immune response, immunoglobulins IgA IgG and IgM